Standardization of 3,5-dinitrosalicylic acid (DNS) assay for measuring xylanase activity: detecting and solving problems - Marko Božinović; Tea Sokač; Anita Šalić; Ana-Marija Dukarić; Marina Tišma; Mirela Planinić; Bruno Zelić (Croatian Journal of Food Science and Technology, 2023)
The 3,5-dinitrosalicylic acid (DNS) assay has been used for many years mainly to determine the enzymatic activity of xylanase. The assay is based on the detection of reduced sugars. Although the method is widely used, several recent studies have questioned the accuracy of the method. They mainly focused on the detection of side reactions that could lead to a false positive result of the assay. In this study, the basic components of the DNS assay such as buffer preparation, substrate source and concentration, incubation time, reagent preparation, and activity calculation were re-evaluated. Potential problems were detected and a new assay procedure was proposed. Compared to literature data, the new assay is shorter because it avoids the generation of a calibration curve and takes into account the enzyme and substrate amount when calculating enzyme activity, which is neglected in current assays.